Pengembangan Sistem Informasi Penelitian dan Pengabdian Masyarakat (PPM) di Akademi Teknik dan Keselamatan Penerbangan Makassar - Nur, Mulyadi; Sabur, Fatmawati (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2019)
LPPM (Institute for Research and Community Service) is an activity unit that manages all research and community service activities carried out by teachers in improving the quality of these supervisors. At this time research or service data is still managed manually by using the Microsoft Excel application as well as Word. This requires inefficient time when manipulating data to make a report. Delete this with a recording model like this can also be moved because of mistakes either intentional or unintentional. The purpose of this study is to build a computer-based information system that can be used to facilitate the performance of the PPM Center in organizing the results of PPM activities. This type of research is a qualitative descriptive study, a series of activities or processes to reveal in-depth information processes that are used as a basis in designing information systems. The results of this research concluded that: (a) this information system can be used as a system that monitors research and service activities, and the absorption of research funds. (b) processing research data more efficiently and can be accessed anywhere and anytime because it is designed using responsive frameworks